The Prevalence of Bacteriuria in Pregnant Women - Ibraheem, M. A.; Diwan, I. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research was conducted in (Baghdad Teaching hospital) and (Al-Alwiya obstetrics hospital). The Samples were as follows : (150) (Pregnant women) in different times of pregnancy. (25) Married women (non pregnant) . (25) Un married women Capable of pregnancy . The range of their ages was (18-45) years. (10) Samples were taken from pregnant women with no evidence of infection as (Control) for the comparison of number and type of bacteria which exists naturally (in area surrounded external opening of urinary duct) (Urethral meatus) of the infected pregnant women . The result showed that Staphylococcus Saprophyticus is a common Cause in these infections .appearing in (19%) of the studied group, while klebsiella was (17.2%), proteus mirabilis bacteria was (14.7%). In married women, Klebsiella pneumoniae was the main cause of urinary infection (33.3%). In unmarried women , Escherichia coli scored the highest occurence (52%).